Knowledge and Attitude towards Basic Life Support Among Healthcare Professionals in Primary Health Care Centers in Hai Al-Andalus, Tripoli - Ali Ghareba (Libyan Medical Journal, 2026)
Basic Life Support (BLS) is a critical component of the chain of survival in cardiac arrest management. In Libya, healthcare professionals are the first line of defense, yet empirical data regarding their BLS proficiency in primary care settings is limited. This study evaluated the knowledge of and attitudes toward Basic Life Support (BLS) guidelines among various healthcare professional categories in primary healthcare (PHC) centers within the Hai Al-Andalus municipality in Tripoli, Libya. A prospective, descriptive cross-sectional study was conducted between August and December 2022. A self-administered questionnaire was distributed to a random sample of Libyan healthcare providers, including doctors, dentists, pharmacists, nurses, and laboratory workers. Data were analyzed using independent t-tests and Chi-square tests, with statistical significance set at p < 0.05. A total of 399 participants completed the survey (99.75% response rate), with a female majority (90.5%) and a mean age of 37.9 ± 8.0 years. While a positive attitude and a strong desire for further BLS training were expressed by over 75% of participants across all specialties, the overall knowledge scores were below average. Doctors demonstrated the highest proficiency (51.6% good knowledge), whereas laboratory workers and nursing staff exhibited significantly lower scores (45.6% and 37.6% below average, respectively; p = 0.001). A critical gap was identified, as a vast majority had never received formal or recent BLS training, primarily due to busy clinical schedules. There is a significant deficiency in theoretical BLS knowledge among PHC professionals in Tripoli, despite highly positive learning attitudes. Immediate institutional interventions are essential to integrate mandatory, regular BLS certification and in-situ simulation training into the primary healthcare professional framework to ensure patient safety and improve survival outcomes